Análisis del noticiero Ayllupak Kawsay, en la identidad cultural de los habitantes de las parroquias Riobamba-rurales período marzo - agosto 2017. - Àngel Geremias, Pilatuna Lasso (2018)
The following research work entitled "ANALYSIS OF THE AYLLUPAK KAWSAY NEWSCAST, IN THE CULTURAL IDENTITY OF THE POPULATIONS OF THE RURAL PARISHES OF RIOBAMBA- PERIOD MARCH - AUGUST 2017" it was designed with the aim of strengthening the cultural identity of the indigenous peoples that correspond to the 11 rural parishes of Riobamba canton through a newscast in Kichwa broadcast by channel 29 Ecuavision. It begins with the analysis of the problem and the definition of the general and its specific, to continue with the theoretical framework where reference is made up of topics and sub-themes related to the independent variable that the analysis of the Ayllupak Kawsay newscast and the dependent variable, it means development of the cultural identity, continuing with the definition of terms, hypothesis, di outcomes and operationalization of the variables. The research methodology, the illustration of the methods, the type and design of the research, the population with 397 inhabitants, the techniques and data collection instruments and the analytical techniques for the study, the technique was applied and the interview were incorporated into the instruments that the survey and interview guide, with data was processed to perform the analysis and interpretation of the results to determine their deduction with the percentages gotten. The data obtained from the survey served to establish the conclusions and recommendations. A high-impact of the research was determined in which visitors allowed to see the great interest that citizens have in listening the news in their own language, which requires them to expand their coverage with interviews and news from the scene, They also raise the need for television to disseminate their customs and traditions to improve the sightseeing tours of citizens al large.